More movement with manure: increased mobility of erythromycin through agricultural soil in the presence of manure - Christine B. Georgakakos; Carmen Enid Martínez; Damian E. Helbling; M. Todd Walter (IWA Publishing, 2023)
Antibiotic residues in the environment threaten soil and aquatic organisms and human and livestock health through the building of antimicrobial resistance. Manure spreading associated with animal agriculture is one source of environmental antibiotic residues. To better understand the risk of contamination, we studied the adsorption of erythromycin, a model macrolide antibiotic used across human and animal medicine. We conducted a series of equilibrium batch experiments to determine the kinetics and extent of adsorption and a continuous-flow column adsorption experiment to observe non-equilibrium adsorption patterns. We determined that the adsorption equilibration time to soil was approximately 72 h in our batch experiments. Erythromycin adsorbed to soil relatively strongly (K = 8.01 × 10−2 L/mg; qmax = 1.53 × 10−3 mg/mg), adsorbed to the soil in the presence of manure with less affinity (K = 1.99 × 10−4 L/mg) at a soil: manure ratio of 10:1 by mass, and did not adsorb to manure across the solid ratios tested. We observed multi-phased adsorption of erythromycin to the soil during the non-equilibrium column experiment, which was largely absent from the treatments with both soil and manure present. These results suggest that erythromycin is more mobile in the environment when introduced with manure, which is likely the largest source of agriculturally sourced environmental antibiotics. HIGHLIGHTS Erythromycin favored its aqueous phase when manure and manure-DOM were present.; Erythromycin may display biphasic adsorption tendencies with multiple mechanisms.; Manure management recommendation: reduce manure erythromycin content prior to field application when contaminant is aqueous.;